Application of laser anemometry in acoustic measurement standards - MacGillivray, Thomas Joseph (The University of Edinburgh, 2002)
The absolute measurement of acoustic particle velocity using Laser Doppler Anemometry (LDA) provides the basis for a method of microphone calibration. In this thesis, after the current standardized calibration method (called reciprocity) is explained, the application of LDA to the determination of sound pressure acting on a microphone is discussed. From a measurement of the output voltage for a given sound pressure, the sensitivity of the microphone can be calculated. In LDA, there are two different techniques for detecting and analysing the Doppler signal generated by acoustic particle motion: continuous detection followed by frequency or time domain analysis, and photon correlation. After a brief discussion of the theory of both methods, their application to measurements within a standing-wave tube is investigated. Velocity measurements extracted from Doppler signals are used to derive values of sound pressure, which are compared with probe microphone measurements. The continuous detection and photon correlation LDA systems are used to measure particle velocity amplitude in a standing wave for frequencies between 660 Hz and 4kHz and velocities between 1 mms⁻¹ and 18 mms⁻¹. LDA is applied to the measurement of microphone sensitivity. The frequency response of the probe microphone is characterized relative to the response of a reference microphone. From the frequency response information, the output voltage of the probe microphone, and the LDA derived sound pressure in a standing wave the sensitivity of the reference microphone is established. Using the continuous detection system, the microphone sensitivity is measured to within ±0.1 dB of the sensitivity obtained by reciprocity calibration for frequencies between 660 Hz and 2 kHz. Using the photon correlation system, the sensitivity is measured to within ±0.2 dB for the same frequency range. Initial measurements were performed in a free field environment, using the photon correlation system, to demonstrate the potential for further development of the LDA calibration technique.
Keywords: Laser Doppler anemometry; Acoustic measurement; Electro-acoustics; Sound measurement